2004
DOI: 10.1111/j.1550-7408.2004.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐dependent Transport of [3H](1d)chiro‐Inositol by Tetrahymena

Abstract: The transport characteristics of (1D)chiro-inositol by the ciliate Tetrahymena were examined in competition studies employing [3H](1D)chiro-inositol. (1D)chiro-Inositol transport was competed by unlabeled (1D)chiro-inositol, myo-inositol, scyllo-inositol, and D-glucose in a concentration-dependent manner. Conversely, (1D)chiro-inositol competed for [3H]myo- and [3H]scyllo-inositol transport. Lineweaver-Burke analysis of the competition data indicated a Km of 10.3 mM and a Bmax of 4.7 nmol/min/mg for (1D)chiro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…For the ciliate Tetrahymena vorax, for example, it was found that the most frequently occurring epimers myo-, scyllo-, and D-chiroinositol were transported across the plasma membrane (Kersting and Ryals, 2004). Similarly, it was shown for human HepG2 liver cells that myoinositol and D-chiroinositol are transported by the same protein (Ostlund et al, 1996).…”
Section: Atint2 Is a Plasma Membrane-localized H 1 Symporter That Difmentioning
confidence: 92%
“…For the ciliate Tetrahymena vorax, for example, it was found that the most frequently occurring epimers myo-, scyllo-, and D-chiroinositol were transported across the plasma membrane (Kersting and Ryals, 2004). Similarly, it was shown for human HepG2 liver cells that myoinositol and D-chiroinositol are transported by the same protein (Ostlund et al, 1996).…”
Section: Atint2 Is a Plasma Membrane-localized H 1 Symporter That Difmentioning
confidence: 92%
“…Phosphatidylinositol that contains a scyllo ‐ or chiro ‐Ins headgroup rather than a myo ‐Ins headgroup has been reported (Carstensen et al 1999; Futerman et al 1985; Kersting and Ryals 2004; Mato et al 1987; Ryals and Kersting 1999). Our results indicate that each inositol isomer tested can serve as substrate for T. vorax PtdIns synthase in vitro with the order of substrate preference being myo ‐Ins> scyllo ‐Ins>(1 d ) chiro ‐Ins> epi ‐Ins>(1 l ) chiro ‐Ins> allo ‐Ins> muco ‐Ins.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge no data are available on the comparative kinetics. Previous work has shown that Tetrahymena transport myo-, scyllo-, and (1D)chiro-Ins by a sodium-dependent mechanism and that each of these inositol isomers is utilized to form the corresponding PtdIns (Kersting and Ryals 2004;Kersting et al 2003;Ryals and Kersting 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inositol exists as a number of stereoisomers, the most common of which is myo-inositol, but other isomers are also present in cells including scyllo -, neo -, epi-D-chiro - and muco-inositols. In T. vorax , non- myo -inositols have also been detected, with evidence that these can be taken up from the medium(Kersting et al, 2003; Kersting and Ryals, 2004; Ryals and Kersting, 1999). Conversion between inositol isomers may also occur via inositol epimerases(Sun et al, 2002), though no conclusive genetic or biochemical data have been published in Tetrahymena to date.…”
Section: Studies On Membrane Lipids In Tetrahymenamentioning
confidence: 99%